DETERMINATION OF RESIDUAL SOLVENTS IN PAROXETINE BY HEADSPACE GAS CHROMATOGRAPHY - , ABDUL RAHAMAN SK; PADMAVATHI SAKINALA; HAREKRISHNA ROY; HAREKRISHNA ROY (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: A simple and sensitive gas chromatographic method was developed and validated for simultaneous determination of acetone and isopropyl alcohol in paroxetine. Methods: The separation was achieved on ZB-1, 30 m length × 0.53 mm ID, and film thickness 5 μm using a flame ionization detector (FID) with gradient column oven temperature program. The injection was carried out in split mode, with a split ratio of 10:1. Dimethylacetamide was selected as a diluent to obtain good sensitivity along with the recovery. 1-propanol was used as an internal standard which employed for area ratio method. Results: The developed gas chromatographic method offers symmetric peak shape, good resolution of 2.3 min, and reasonable retention time for the solvents acetone 9.210 min and isopropyl alcohol 9.845 min. The limit of detection for acetone and isopropyl alcohol was 26.72 μg/ml and 82.96 μg/ml, respectively. Limit of quantitation for acetone and isopropyl alcohol was 80.96 μg/ml and 251.39 μg/ml, respectively. Precision was 0.83 and 0.63. Linearity was y = 0.0004x, R2 = 0.9988 for acetone, and y = 0.0001x+0.0021, R2 = 0.9987 for isopropyl alcohol, and accuracy along with robustness is performed and acceptable results were obtained. Conclusion: The proposed, developed method was demonstrated to be simple, sensitive, linearity, accurate, and robust, hence can be used to determine the residual organic solvents in paroxetine drug substance and drug product.